Geographic Information System of Distribution of Poor Households in the Palaran District - Kevin Rivaldi Sosang; Syafei Karim; F.V Astrolabe Sian Prasetya (Politeknik Pertanian Negeri Samarinda, 2022)
Related to poverty, an important issue that needs attention is the relatively large number of poor people. This relatively large number of poor people is mainly associated with poverty alleviation efforts, both through funding by the central government and local governments. However, such a high-quantity effort has not been able to significantly alleviate poverty. This can be seen from the worsening quality of the poor. So to get these results, a geographical information system (GIS) is needed or commonly known as a geographic information system (GIS) so that data on poor households is right on target. A geographic Information System is a tool that can be used to assist in analyzing the condition of an area in the field of the population to determine the level of welfare of its population. GIS can also convey information in the form of thematic maps so that the condition of an area towards poverty can be presented in the form of visualization of thematic maps and can make it easier for users to understand the information conveyed. The expected result is that this GIS application can make it easier to provide information to the public about the existence of poor households in the Palaran District.